3x-6+5=2(5x-4)

Simple and best practice solution for 3x-6+5=2(5x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6+5=2(5x-4) equation:


Simplifying
3x + -6 + 5 = 2(5x + -4)

Reorder the terms:
-6 + 5 + 3x = 2(5x + -4)

Combine like terms: -6 + 5 = -1
-1 + 3x = 2(5x + -4)

Reorder the terms:
-1 + 3x = 2(-4 + 5x)
-1 + 3x = (-4 * 2 + 5x * 2)
-1 + 3x = (-8 + 10x)

Solving
-1 + 3x = -8 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-1 + 3x + -10x = -8 + 10x + -10x

Combine like terms: 3x + -10x = -7x
-1 + -7x = -8 + 10x + -10x

Combine like terms: 10x + -10x = 0
-1 + -7x = -8 + 0
-1 + -7x = -8

Add '1' to each side of the equation.
-1 + 1 + -7x = -8 + 1

Combine like terms: -1 + 1 = 0
0 + -7x = -8 + 1
-7x = -8 + 1

Combine like terms: -8 + 1 = -7
-7x = -7

Divide each side by '-7'.
x = 1

Simplifying
x = 1

See similar equations:

| y-84/2=7 | | X^2+DX-2D^2=0 | | 5p/6-15=-10 | | -6-m/6-8=0 | | v-404/17=31 | | K-12/4=8 | | 6n=30+3[n-4] | | 11+3d=89 | | 24-3k=15 | | 7(z-88)=84 | | 558.25/14.5 | | 120=6(2x+6) | | 15+8c=95 | | 7i(3-5i)= | | Y+4x=13 | | 6(3x+-4)=12 | | 6(3x/2-x)=6(x/6-2/3) | | 21-(x-5)= | | 2.5(x+6)=75x | | .2(y-3)=-3(y-5) | | 0.33(6x-12)=0 | | 128=2(8x-8)+2x | | 16p^2-8p-3= | | 19(x+19)=x+29 | | 2.75x+3=1.75x+7 | | 78=(-2m+3)+m | | -0.55p-5=0.45p | | 0=2x+1+lnx | | x(3500)+y(2500)=17255 | | (6-4w+4y)(-8)= | | 180/25 | | 10-3(2x-3)=13 |

Equations solver categories